Polyamine adsorbents for gas separation using humidity swing regeneration step
By using a solid adsorbent with a porous network with a polymeric amine with an average molecular weight of more than 2000 Daltons, the problem of instability of existing adsorbents in the presence of high relative humidity and water is solved, and efficient and durable adsorption performance is achieved.
Patent Information
- Application Number
- CN202380018701.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-08
- Filing Date
- 2023-02-08
- Publication Date
- 2025-02-07
AI Technical Summary
The existing adsorbents exhibit instability in the presence of high relative humidity and water, resulting in a decrease in adsorption capacity and prolonged circulation time, making it difficult to meet the requirements for efficient and durable adsorbents in industrial separation.
A solid adsorbent consisting of polymeric amines with an average molecular weight of more than 2000 Daltons, forming a porous network, and insoluble in water, suitable for granular, film or sheet form. The adsorbent is supported on an inorganic porous support or integrated in a solid porous polymer network, enhancing its stability and adsorption capacity.
The adsorbent remains stable in the presence of high relative humidity and water, significantly improving the adsorption capacity and cycle times of carbon dioxide, reducing the processing cycle time, and improving the durability and efficiency of the adsorbent.
Smart Images

Figure CN119403619A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present invention generally relate to solid amine adsorbents, adsorptive contactors, and methods for using them for adsorptive gas separations of multi-component fluid streams. More particularly, embodiments of the present invention relate to polymeric amine adsorbents supported on inorganic porous supports or integrated in solid porous polymer networks, having improved stability to moisture and / or oxygen and rapid carbon dioxide adsorption capacity; to adsorptive contactors having polymeric amine adsorbents; and to methods for using them for adsorptive gas separations of acid gases from multi-component fluid streams. Background Art
[0002] Adsorption separation processes are common in industrial separation processes and are considered for use in applications that mitigate the negative impacts of greenhouse gas emissions and associated climate change. For example, adsorption gas separation processes can be used to separate carbon dioxide from a multi-component fluid stream (e.g., air, flue gas, or process gas). The cost of an adsorption separation process is largely affected by the amount of adsorbent required to produce a specific production volume of purified product. The production volume per mass of adsorbent is a simple product of the adsorption cycle capacity and the adsorption cycle time. In adsorption gas separation processes using temperature swing or chemical swing desorption mechanisms, the desorption of adsorbed molecules or components may be a relatively slow process due to the need to introduce desorption energy into the system and effectively transfer the energy to the adsorbent.
[0003] During the regeneration step of the adsorptive gas separation process, in some cases, steam can enter the adsorptive separator to contact and directly heat the adsorbent material and / or purge the separation components from the adsorptive separator. Water in the product stream can then be separated from the product stream by condensation, thereby increasing the purity of the remaining stream.
[0004] Desorption of the target component by humidity swing can provide a rapid and efficient means of desorbing the adsorbed component while producing a product stream that can be further purified by condensing gaseous water from the product stream. Benefits of humidity swing or relative humidity swing for desorption include: 1) rapid introduction of energy by using the heat of adsorption or condensation of moisture to distribute thermal energy relatively evenly throughout the porous adsorbent; 2) water can be discharged to the atmosphere when desired and when there is no significant contamination and it is permitted; and 3) adsorbents with significant water adsorption capacity are quite common.
[0005] Disadvantages of exposing conventional adsorbent materials to water and / or steam in adsorptive separation processes include: 1) water is strongly adsorbed on the adsorbent material and can result in energy intensive and slow drying of the adsorbent material, which can result in slow or long process cycle times; 2) the adsorbent material may degrade in the presence of water (e.g., polymeric amine adsorbents can migrate due to local dissolution, thereby making the amine mobile, which results in loss of the amine from the adsorbent material, and for metal-organic framework (MOF) adsorbents, their structures may undergo phase changes in the presence of steam, resulting in pore collapse and / or loss of selected adsorption capacity), and / or 3) the water stability attributes of the adsorbent material are often opposite to one or more desired attributes (e.g., target component adsorption capacity and / or reaction kinetics).
[0006] Moreover, conventional adsorptive gas separators and methods typically use an adsorbent having a single adsorbent material, wherein the regeneration step can include: allowing steam to enter the adsorption bed through an inlet; flowing the steam into contact with the adsorbent material in the adsorption bed; desorbing the target component to form a product stream; and recovering the product stream from the adsorption bed through an outlet or port.
[0007] Polymeric amines are well suited for some adsorptive gas separation applications relative to other adsorbents because of their higher affinity, selectivity, large adsorption capacity, and reaction kinetics for capturing target components, such as carbon dioxide (referred to herein as "CO2"). However, polymeric amines with high primary and secondary amine content are generally water-soluble polymers, which presents a challenge when using them as solid adsorbents in processes that expose them to high relative humidity, condensate, and / or water, since moisture tends to leach out the amines. This drawback limits conventional solid adsorbents that vary such polymeric amines to applications where the adsorbent is exposed to dry or low relative humidity conditions, such as gas chromatography applications. Moreover, polymeric amines with high primary and secondary amine content tend to have limited stability when exposed to oxygen at elevated temperatures.
[0008] In order to commercially adopt adsorptive gas separations, it is necessary to reduce life cycle costs and increase adsorbent durability.Therefore, there is a need for enhanced adsorptive gas separation processes and adsorbents having desirable selectivity, high adsorption capacity (adsorption capacity), fast reaction kinetics, and high durability. Summary of the invention
[0009] In an embodiment, a solid adsorbent is disclosed, the solid adsorbent comprising a polymeric amine having an average molecular weight greater than 2000 Daltons, wherein the solid adsorbent is insoluble in water, forms a porous network, and is in the form of particles, films, or sheets.
[0010] In a broad aspect, an adsorptive gas separation process for separating a first component from a multicomponent fluid stream, the multicomponent fluid stream having at least a first concentration of the first component and a second component, the process comprising: 1) providing an adsorptive gas contactor with a solid adsorbent comprising a polymeric amine having an average molecular weight greater than 2000 Daltons, wherein the solid adsorbent is insoluble in water, forms a porous network, and is in the form of particles, films, or sheets; 2) passing the multicomponent fluid stream through the adsorptive gas contactor; 3) adsorbing at least a portion of the first component from the multicomponent fluid stream onto the solid adsorbent; 4) forming a first product stream; and 5) recovering the first product stream from the adsorptive gas contactor, wherein the concentration of the first component in the first product stream is less than a first concentration of the first component in the multicomponent fluid stream; 5) desorbing at least a portion of the first component adsorbed on the solid adsorbent to form a second product stream; 6) recovering the second product stream from the adsorptive gas contactor, wherein the second product stream is enriched in the first component relative to the multicomponent fluid stream, such that the concentration of the desorbed first component in the second product stream is greater than the first concentration of the first component in the multicomponent fluid stream.
[0011] In embodiments, the disclosed solid adsorbent can include at least a polymeric amine formed into a porous solid, the polymeric amine having an equilibrium capacity for CO2. In embodiments, the ratio of the equilibrium capacity for CO2 to the heat capacity of the solid adsorbent can be 15 to 40 cc stp CO2 / (J / K) (stp = standard temperature and pressure) per unit heat capacity of the solid adsorbent, wherein the equilibrium capacity is measured at 50°C at a 15% CO2 feed mixture. In embodiments, the solid adsorbent can have a kinetic adsorption rate, wherein the kinetic adsorption rate is greater than 0.03 mmol / g / s when contacted with a CO2 mixture, wherein the CO2 mixture contains 15% CO2 and the temperature is between 30°C and 50°C, and can have a heat of adsorption for CO2, wherein the heat of adsorption for CO2 is between 70 and 120 kJ / mol of adsorbed CO2.
[0012] In an embodiment, the disclosed adsorption gas contactor can include a plurality of adsorbent sheets, each sheet including a solid adsorbent. In an embodiment, the thickness of each adsorbent sheet can be in the range of 0.1 mm to 3 mm, or preferably in the range of 0.2 mm to 1 mm. The plurality of sheets can be positioned to form a channel between them, thereby enabling or otherwise allowing a gas flow to flow between and through the channel and contact the adsorbent sheet. In an embodiment, the density of each of the plurality of solid adsorbent sheets can be 0.2 g / cm 3 Up to 0.8g / cm 3and include polymeric amine polymers having greater than 5 weight percent nitrogen from primary or secondary amine functional groups, wherein the polymeric amine can be formed from a copolymer of a vinylamine monomer having a molecular weight less than 100 Daltons and a divinyl monomer having a molecular weight greater than 100 Daltons, or formed by the reaction of a water-soluble polymeric amine with a long chain alkyl (8 carbons or more) group. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1a is a perspective view showing a pair of adsorbent sheets, each sheet having a planar shape and defining a channel therebetween, thereby forming a pair of adsorbent sheets;
[0014] Figure 1b is based on Figure 1a The cross-sectional view of the adsorbent sheet shown along section AA has a flat or planar cross-section;
[0015] Figure 1c is a cross-sectional view of an adsorbent sheet having a square wave cross section;
[0016] Figure 1d is a cross-sectional view of an adsorbent sheet having a bending wave cross section;
[0017] Figure 1e is a cross-sectional view of an adsorbent sheet having a triangular wave cross section;
[0018] Figure 1f is a cross-sectional view of an adsorbent sheet having a zigzag cross section;
[0019] Figure 1g is a cross-sectional view of an adsorbent sheet having a corrugated cross section;
[0020] Figure 2 is a process flow diagram of an embodiment of an adsorptive gas separation method using a polymeric amine adsorbent or a polymeric amine composite adsorbent for separating a first component from a multi-component fluid stream;
[0021] Figure 3a is a scanning electron micrograph surface image of a polyethyleneimine adsorbent sheet supported on porous silica at 500 times magnification;
[0022] Figure 3b is a scanning electron micrograph surface image of a polyethyleneimine adsorbent sheet supported on porous silica at 10,000 times magnification;
[0023] Figure 3c is a cross-sectional scanning electron micrograph of a polyethyleneimine adsorbent sheet supported on porous silica at 5000 times magnification;
[0024] Figure 4is a graph of particle size and distribution of the copolymer of allylamine and divinylbenzene (DVB) adsorbent of Example 6B, wherein the y-axis represents volume as a percentage and the x-axis represents particle size (micrometers);
[0025] Figure 5a is a bar graph comparing two different adsorbents and their oxidative stability after exposure to air at 120 °C for 1 hour, after 1 cycle, and after 20 cycles;
[0026] Figure 5b is a bar graph showing four different adsorbents and their hot water stability after the adsorbent powders are soaked in hot water;
[0027] Figure 6a is a scanning electron micrograph of the adsorbent powder at 55,000 times magnification;
[0028] Figure 6b is a scanning electron micrograph of a cross section of the adsorbent sheet from Example 8 showing the polymer particles and porosity at 55,000 times magnification; and
[0029] Figure 7 is a graph of the temperature and mass of an adsorbent sheet sample as a function of time. The mass of the sample is the solid line graph, while the temperature is the dashed line graph. The mass and temperature are represented on the right and left y-axes, respectively, while time is represented on the x-axis. DETAILED DESCRIPTION
[0030] definition:
[0031] Adsorbent: A porous solid material capable of adsorbing molecules on and / or in the adsorbent material by chemisorption and / or physisorption.
[0032] The terms "sorbent," "adsorbent," and "absorbent" are used interchangeably herein.
[0033] The terms "sorbed," "adsorbed," and "absorbed" are used interchangeably herein.
[0034] Tolerant Adsorbent: An adsorbent that meets or exceeds the definition of at least one of a steam tolerant adsorbent, an oxidation tolerant adsorbent, a nitrogen oxide (herein referred to as "NOx") tolerant adsorbent, and / or a sulfur oxide (herein referred to as "SOx") tolerant adsorbent.
[0035] Intolerant Adsorbent: An adsorbent that fails to meet or exceed the required definition of at least one of a steam tolerant adsorbent, an oxidation tolerant adsorbent, a NOx tolerant adsorbent, and / or a SOx tolerant adsorbent.
[0036] Composite adsorbent: An adsorbent comprising two or more adsorbent materials of different composition and / or different pore structure, for example, at least one stable or tolerant adsorbent and at least one unstable or intolerant adsorbent, combined to form an adsorbent mixture, wherein the two or more adsorbent materials can be substantially uniformly or non-uniformly distributed within the adsorbent mixture.
[0037] Adsorbent sheet: A self-supporting sheet, active layer or laminate having a thickness between 0.1 mm and 3.0 mm with at least one other dimension being 100 times greater than the thickness. The adsorbent sheet can be cut into tapes wherein the width of the tape is at least 10 times greater than the thickness of the sheet.
[0038] Adsorbent configuration or formed composite adsorbent: A solid object comprising at least one adsorbent configuration, such as an aggregated powder, with or without a binder or adsorbent support, formed into an object of at least one millimeter in size or larger, such as pellets, beads, irregular particles, ribbons, rings, sheet segments, which can be used in a contactor vessel or column or an adsorbent contactor to provide a passage for a process fluid.
[0039] Supported composite adsorbent: A composite adsorbent (eg, adsorbent sheet) on an adsorbent support.
[0040] Steam-stable adsorbent: A porous solid material that can maintain an adsorption capacity, adsorption energy, and adsorption kinetics loss of less than 10% after exposure to conditions of >95% relative humidity (hereinafter referred to as "RH") at temperatures between 80 degrees Celsius (hereinafter referred to as "°C") and 120°C for more than 100 hours (hereinafter referred to as "h").
[0041] Vapor unstable adsorbent: A porous solid material that exhibits a greater than 10% loss in adsorption capacity, adsorption energy, and adsorption kinetics after exposure to >95% RH for greater than 100 hours at temperatures between 80°C and 120°C.
[0042] Steam resistant: capable of maintaining less than 10% loss in adsorption capacity, adsorption energy, and / or adsorption kinetics after exposure to steam conditions of >95% relative humidity at temperatures between 80°C and 120°C for greater than 100 hours.
[0043] Resistant to oxidation: Able to maintain less than 10% loss in adsorption capacity, adsorption energy and / or adsorption kinetics after exposure to air at a temperature of about 110°C for more than 4 hours.
[0044] Target cycle capacity: The amount of a suitable target component captured in a separation cycle per unit mass of adsorbent under steady-state operation.
[0045] Cycle capacity: The amount of target component that can be purified or extracted from a product stream per unit mass of adsorbent in an adsorption-desorption separation cycle.
[0046] Heat capacity (referred to herein as "Cp"): The heat capacity of the adsorbent or adsorbent mixture, its support, and other inactive components that are in thermal contact with each other in an adsorbent contactor.
[0047] Heat of Adsorption: The amount of energy released by removing a molecule from the gas phase and causing it to attach to a solid or supporting liquid.
[0048] Water sorbent material: A porous solid material capable of undergoing a weight increase of greater than 5% when exposed to conditions greater than 60% RH.
[0049] Target compound adsorbent material: A porous solid material capable of undergoing a weight increase greater than 1% when exposed to conditions where the feed gas stream or feed mixture is at a temperature between -10°C and 80°C.
[0050] Thickness: The smallest dimension of a three-dimensional object. For sheet-shaped materials, it is measured in a direction perpendicular to the plane of the sheet. For a sphere, it is the diameter of the sphere. For a ring, it is the difference between the outer radius and the inner radius of the ring. For an irregular particle, it is the shortest distance of a line passing from one side of the object to the other side of the object and through the center of mass of the object.
[0051] PEI: Polyethyleneimine or [CH2CH2NH]n polymer, with repeating units of iminoethylene arranged in a linear or branched manner. Linear PEI contains all secondary amines, and branched PEI can contain primary, secondary, and tertiary amine groups.
[0052] PAA: polyallylamine or [CH2CHCH2NH2]n
[0053] Domain: A fragment of a molecule or polymer that is considered to be separate from the rest of the molecule or polymer from a solubility point of view.
[0054] Channel voidage: The voidage of the channels formed by the adsorbent sheet or adsorbent configuration within the contactor. Channel voidage can be used interchangeably with the term channel voidage.
[0055] Particle: A piece of material with a volume equal to or less than 1 cubic millimeter.
[0056] Particle Size: The size of a solid particle, when not specified, defined as the equivalent diameter of a sphere of the same volume as the particle.
[0057] Film: A thin layer of material deposited on a support or near the surface of a sheet of material.
[0058] Sheet: An object in which one dimension is much smaller than two other dimensions, giving the object the appearance of a two-dimensional object or surface. As used in some embodiments described herein, a solid object is called a sheet when the smaller dimension, defined as the shortest distance between two points on opposite sides of the object, is less than an average of 1% of the length of any line along the surface of the object connecting two opposite edges of the object.
[0059] Strip: An object with one dimension much smaller than the two other dimensions, where the length of the object is significantly different relative to the two other dimensions. Strips can be obtained by cutting sheets into narrow strips. As used in some embodiments described herein, the flat width of the strip is at least 20 times smaller than the flat length, and the thickness is less than 1% of the flat length of the object. The strip can be bent, warped, pleated, or corrugated, for example, to help form flow channels when assembled into a contactor.
[0060] Insoluble: Less than 100 ppm by weight of solid material when dissolved in a suspension containing 1% solids per solvent in an aqueous solution at a pH of 5 to 9 at a temperature between 10°C and 40°C.
[0061] Generally, porous adsorbent structures are disclosed. In embodiments, the porous adsorbent structure can include polymeric amine adsorbent sites that are selectively supported on an inorganic porous support or integrated into a porous polymer network. In embodiments, such adsorbent structures can be advantageously used in adsorptive gas separation methods. More particularly, the components and structures of such adsorbent structures can be used in methods of separating acid gases from a multi-component fluid stream (e.g., a combustion gas stream, a flue gas stream, a process gas stream, an air stream, or other dilution source) in an adsorptive gas separation method, wherein the polymeric amine adsorbent is exposed to at least one process gas stream (e.g., a feed stream and / or a regeneration gas stream) at high relative humidity (e.g., greater than about 30% relative humidity).
[0062] The effects of conditioning a polymeric amine adsorbent on at least a portion of a separation process cycle while being exposed to high relative humidity that can cause significant amounts of liquid water to adsorb or fill some of the adsorbent pores are described.
[0063] New polymeric amine adsorbents having high adsorption capacity for at least one component and high stability and / or tolerance to moisture, oxygen (hereinafter referred to as "O2") and carbon dioxide (hereinafter referred to as "CO2") are described herein. In embodiments, such polymeric amine adsorbents may be supported on a support material having a high pore volume.
[0064] Polymeric amines having higher primary and secondary amine contents are generally water soluble polymers and are known to become mobile or leach from the adsorbent support and / or adsorption contactor when exposed to high relative humidity. As described herein, chemical modification of amine polymers can be used to modify the polar properties of polymeric amines, thereby reducing the tendency of the amines to leach and / or resulting in the immobilization of the amines within the porous solid support.
[0065] The use of known supported polymeric amine adsorbents is generally limited to applications where the adsorbent is only exposed to dry or low relative humidity conditions and / or is protected from exposure to high relative humidity or water, such as in gas chromatography applications. As new applications for adsorption processes for separation of multicomponent gas mixtures containing water and / or regeneration using steam or hot water are developed, there is a need to develop more stable and robust adsorbents.
[0066] Also disclosed are copolymerized amine monomers having bulky rigid copolymers that facilitate the formation of porous network structures, which have similar benefits in acid gas removal under humid conditions.
[0067] Described herein are preferred macroscopic arrangements of polymeric amine adsorbents in two-dimensional structures for building practical contactors with reduced flow resistance and enhanced acid gas recovery.
[0068] One aspect of the adsorbent is the macroscopic or three-dimensional structure of the adsorbent, which in some embodiments can exhibit a porous network geometry comprising a primary pore network having interconnected primary pores and a secondary pore network having interconnected secondary pores, wherein the primary pore network is interconnected with the secondary pore network. In an embodiment, the average diameter of the primary pores is in the range of about 1 micron to about 30 microns, and the average pore size of the secondary pores is in the range of about 10 nanometers to about 200 nanometers.
[0069] Some enhanced rapid cycle adsorptive gas separation methods use a humidity swing desorption mechanism to regenerate a solid adsorbent. Such adsorptive gas separation methods can be used to separate undesirable components, such as CO2, from a gas mixture to help address greenhouse gas (GHG) emissions and related climate change challenges. Examples of such methods are described in International Published Patent Application WO2017 / 165974.
[0070] There is a need for polymeric adsorbents that have high cyclic capacity for adsorption and desorption of target molecules, as well as suitable chemical and structural stability of the active component when exposed to its processing environment, and that retain active site functionality as well as kinetically accessible those sites.
[0071] The durability of the adsorbent material to cyclic exposure to high relative humidity, condensate, water and / or oxygen is critical in some applications as described above. Embodiments of polymeric amine adsorbents having stable active adsorption sites within a porous structure are described herein, wherein target gas components can be readily introduced and separated.
[0072] Example
[0073] In embodiments, the solid polymeric amine adsorbent can have an average molecular weight greater than about 2000 Daltons, be insoluble in water, and be configured as particles or films having a porous network. In embodiments, the solid polymeric amine adsorbent can include a first adsorbent domain (soluble domain) that is soluble in water and a second adsorbent domain (insoluble domain) that is insoluble in water. In embodiments, the solid polymeric amine adsorbent can also have a nitrogen content greater than about 6% by mass relative to the total mass of the polymer. In other embodiments, the solid polymeric amine adsorbent can contain primary amine groups, secondary amine groups, and tertiary amine groups. In some embodiments, the tertiary amine groups account for less than about 20% mole fraction of nitrogen in the polymeric amine adsorbent. In some embodiments, the primary amine groups and secondary amine groups account for more than about 80% mole fraction of nitrogen in the polymeric amine adsorbent. In some embodiments, the solid polymeric amine adsorbent can have an average pore volume greater than about 0.2 ml / g, or preferably an average pore volume in the range of about 0.3 ml / g to about 1.5 ml / g. In an embodiment, the average BET (Brunauer, Emmett and Teller) surface area of the solid polymeric amine adsorbent can be about 4 m 2 / g to about 500m 2 / g, or more preferably about 20 m 2 / g to about 300m 2 / g, wherein the surface area is measured, for example, using the BET technique with liquid nitrogen.
[0074] In embodiments, the solid polymeric amine adsorbent can have an average pore size in the range of about 10 to about 200 nanometers, for example as measured using a nitrogen adsorption isotherm. In some embodiments, the solid polymeric amine adsorbent is in particulate form with an average particle size in the particle size range of about 0.2 to about 40 microns. In some embodiments, the solid polymeric amine adsorbent described herein is unsupported, forms a porous solid adsorbent, or the adsorbent can be disposed on and / or in an inorganic porous support. In some embodiments, the polymeric amine adsorbent described herein can form a self-supporting active layer comprising at least about 75% by weight of the polymeric amine adsorbent, wherein the thickness of the active layer is in the range of about 0.1 mm to about 3 mm, or in particular about 0.2 mm to about 1 mm.
[0075] In embodiments, the solid polymeric amine adsorbent can be arranged into an adsorbent layer or other adsorbent configuration having a porous network geometry that combines a primary pore network of interconnected primary pores that are also interconnected with a secondary pore network. In certain embodiments, the primary pore network has an average primary pore diameter ranging from about 1 micron to about 30 microns, and the secondary pore network has an average diameter ranging from about 10 nanometers to about 200 nanometers.
[0076] Such adsorbent structures can be formed from porous particles having an average pore size of about 10 nanometers to about 200 nanometers and an average particle size of about 0.2 micrometers to about 40 micrometers. In making an adsorbent layer or other adsorbent configuration, imperfect packing of particles (which can be irregularly shaped) can produce a pore network between particles having an average primary pore size in the range of about 1 micrometer to about 30 micrometers.
[0077] This hierarchy of interconnected pores can facilitate rapid gas exchange between the adsorbent and the process stream.
[0078] In an embodiment, the solid polymeric amine adsorbent can be a polymeric amine composite adsorbent having an average molecular weight greater than about 2000 Daltons, being insoluble in water, and being configured as a particle or film comprising a porous network. In an embodiment, the polymeric amine composite adsorbent can include a first adsorbent domain (soluble domain) soluble in water and a second adsorbent domain (insoluble domain) insoluble in water. In an embodiment, the solid polymeric amine composite adsorbent has a nitrogen content greater than about 6% by mass relative to the total polymer mass. In an embodiment, the solid polymeric amine composite adsorbent comprises primary amine groups, secondary amine groups, and tertiary amine groups. In some embodiments, the tertiary amine groups account for less than about 20% mole fraction of nitrogen in the polymeric amine composite adsorbent. In some embodiments, the primary and secondary amine groups account for more than about 80% mole fraction of nitrogen in the polymeric amine composite adsorbent.
[0079] In an embodiment, the polymeric amine composite adsorbent can include polyethyleneimine having a molecular weight between 2000 and 12000 Daltons, which is reacted with a molecule comprising a C10-C16 alkyl terminal chain and an electrophilic group (the electrophilic group can bind to a primary or secondary amine) to form a functionalized polymer. In an embodiment, the functionalized polymer is deposited on a porous support having an average pore volume between 0.3 and 1.5 ml / g and an average BET surface area of about 4 m 2 / g to about 500m 2 / g, or more preferably about 20 m 2 / g to 300m 2 / g, and the average pore size is in the range of about 10 to 200 nanometers. Examples of such porous support materials include silica, alumina, zirconia, clay, aluminosilicates, their analogs and combinations, as long as the pore size is large enough, for example, greater than 10 nm. The surface area can be measured using the BET technique using liquid nitrogen.
[0080] In embodiments, the polymeric amine composite adsorbent composite can further include ethanolate. The solid composite adsorbent can be unsupported, or disposed on and / or in an inorganic porous support. In embodiments of the polymeric amine composite adsorbent, the polymeric amine can be at least one of a copolymer of a vinylamine having an interconnected porous structure and a divinyl monomer containing primary and / or secondary amine groups.
[0081] In an embodiment, the polymeric amine is at least one of:
[0082] A grafted alkylamine supported on a porous support, wherein the average pore volume of the porous support is between about 0.3 ml / g and about 1.5 ml / g, or preferably about 0.7 ml / g to about 1.5 ml / g, and the grafted functional groups on the amine groups include hydrophobic groups,
[0083] Polyethyleneimine functionalized with a C10-C16 alkyl alcohol and supported on a porous organic or inorganic solid support, and / or
[0084] Polyethyleneimine functionalized by reaction with an alkyl epoxide.
[0085] The porous network polymeric amine composite adsorbent can form a self-supporting active layer comprising at least about 75 wt % of the polymeric amine composite adsorbent, wherein the thickness of the active layer is in the range of about 0.1 mm to about 3 mm, or particularly about 0.2 mm to about 1 mm.
[0086] In an embodiment, the polymeric amine composite adsorbent can include a copolymer of vinylamine and a divinyl monomer having a primary amine group and / or a secondary amine group and an interconnected porous structure. In an embodiment, the polymeric amine composite adsorbent includes a copolymer of allylamine and divinylbenzene (DVB).
[0087] In an embodiment, the polymeric amine composite adsorbent can include a copolymer of propylene imine and divinyl benzene, and / or a copolymer of ethylene imine and divinyl benzene.
[0088] In an embodiment, the composite adsorbent can be synthesized by controlling the reaction stoichiometry of the electrophilic long alkane capping agent and PEI, the reaction temperature and the solvent composition. In an embodiment, when synthesizing a low water-soluble PEI polymer derivative or a polymeric amine composite adsorbent, the fraction of primary or secondary amines reacting with electrophilic molecules can be greater than about 5% and less than about 40%.
[0089] The following is a more detailed description of the resulting adsorbent and composite adsorbent examples demonstrating greater than 80% of the CO2 adsorption capacity of native PEI polymer under the same conditions. However, in brief, Examples 1 and 2 provide the CO2 adsorption capacity of the adsorbent powder and adsorbent sheet, demonstrating that when the adsorbent powder is included in the adsorbent sheet, the CO2 capacity decreases by less than 15%. This difference can be explained by the addition of non-CO2 adsorbent materials to the adsorbent sheet composite.
[0090] Example 3 shows that insufficiently long alkyl chains of alkyl-epoxide functionalizing agents cannot prevent the loss of CO2 capacity of the composite material after immersion in pure water. Similarly, a minimum molecular weight of polyethyleneimine is required to prevent measurable leaching of the amine-containing polymer to the outside of the silica support. Although filling of large membranes or pores by water does not generally occur under cyclic adsorption / desorption conditions for separating CO2 using rapid cycles with steam regeneration, slow migration of amines was observed for adsorbent compositions that failed the liquid water exposure test. Three 1000h (or approximately 50,000 adsorption / desorption cycles) tests were conducted using contactors made of PEI 2K without epoxidation, PEI-2K with C4-epoxy-alkyl functionalization, and PEI 10K with C12-epoxy-alkyl functionalization, respectively. The results of these tests are related to the results of the pass / fail table presented in Example 3.
[0091] Under typical input gas operating conditions, the adsorption capacity of the composite adsorbent is generally greater than about 2 mmol / g when exposed to a nitrogen gas stream containing 15% CO2 at 50°C. Moreover, the disclosed composite adsorbent also demonstrates rapid adsorption kinetics, with an initial adsorption rate greater than about 0.03 mmol / g / s when exposed to 15% CO2 in nitrogen at 50°C, and an average particle size of the adsorbent is less than 30 microns, as derived from the slope of the weight increase of the TGA data. Within the adsorbent contactor, the adsorbent sheet exposed to a high CO2 flow rate per gram of adsorbent exhibits an average kinetic rate magnitude of similar order, as shown by the production rates in Examples 5 and 11. However, the local kinetic rate of CO2 adsorption is at least one order of magnitude faster than the total kinetic rate limited by the feed CO2 flow rate.
[0092] Examples of adsorbent sheets comprising the composite adsorbent described herein, comprising greater than about 75 weight percent amine-containing adsorbent particles having an average particle size in the range of about 0.2 to about 40 microns, demonstrate rapid CO2 adsorption kinetics similar to that of a loose powder thin layer. Figure 3a and 6b Scanning electron micrographs of adsorbent sheets using two different types of amine adsorbent powders are shown, where the major material in the sheet is the adsorbent powder.
[0093] In an embodiment, the polymeric amine adsorbent and the polymeric amine composite adsorbent have a CO2 equilibrium capacity at 50°C at a 15% CO2 feed mixture, a heat capacity per unit of the adsorbent is between 15 and 40 cc CO2 / (J / K), and a kinetic adsorption rate greater than about 0.03 mmol / g / s when the adsorbent (regenerated and ready for adsorption) is contacted with a 15% CO2 mixture at a temperature between 30°C and 50°C.
[0094] Examples 2 and 8 represent adsorbent sheets made from two different adsorbent materials comprising amine polymers. The heat capacity (Cp) of the adsorbent sheets presented in Examples 2 and 8 is between 1.7 J / gK and 2 J / gK, resulting in greater than 15 cc CO2 capacity / (J / K) adsorbent sheet heat capacity. This ratio strongly affects the amount of energy used in adsorbent regeneration when desorbing CO2. A larger ratio improves the economics of the process when other parameters are not changed.
[0095] In an embodiment, the heat of adsorption of CO2 by the polymeric amine composite adsorbent is between 70 and 120 kJ / mol of adsorbed CO2.
[0096] The heat of CO2 adsorption also affects the energy cost of regenerating the adsorbent. Lower heats of adsorption are preferred, however, selective adsorption of CO2 requires sufficient thermodynamic driving force to remove CO2 from a low CO2 partial pressure supply.
[0097] In some embodiments, the adsorption capacity loss of the polymeric amine composite adsorbent is less than 10% after 50,000 operation cycles, wherein the operation includes a regeneration step under hot and humid conditions, for example, at a temperature between 90° C. and 130° C. and at a relative humidity ranging from 50% to 100%.
[0098] In some embodiments, the functional amine groups form greater than about 50% of the amine groups present in the amine polymer, wherein the functional amine groups can include at least one of:
[0099] R1-CH2-NH2
[0100] R1-C2H4-NH2
[0101] R1-COR2-CH2-NH2
[0102] R1-NH-R2
[0103] R1-NH-CH2-COR2,
[0104] wherein R1 and R2 are one of the following: hydrogen, a polyamine, a copolymer of a vinylamine and a rigid divinyl spacer group, an alkane, or a linear alkane chain of 10 to 16 carbons.
[0105] In an embodiment, the polymeric amine adsorbent can be formed as a copolymer by reacting a short (molecular weight less than 100 Daltons) vinyl amine monomer with a long (molecular weight greater than 100 Daltons) divinyl monomer.
[0106] The measure of the processing intensity of an adsorbent system can be expressed as metric tons of gas components captured from a gas mixture per metric ton of adsorbent per day (referred to herein as "TPD / MT"). Key parameters that affect processing intensity include the capacity and kinetics of the adsorbent. Adsorbents with high adsorption capacity and fast kinetics are generally well suited for increasing processing intensity. Examples of the productivity of two different adsorbent contactors operating under rapid cycle conditions are provided in Examples 5 and 11 presented below.
[0107] In an embodiment, a contactor comprising a sheet of a novel adsorbent, a polymeric amine adsorbent, or a polymeric amine composite adsorbent demonstrates a processing intensity of greater than 30 metric tons / day of CO2 capture per metric ton of adsorbent from a gas mixture having a 10% CO2 concentration when cycling between adsorption and desorption steps is less than 2 minutes.
[0108] Adsorbent sheet or adsorbent configuration and separator or contactor
[0109] Embodiments of the present invention include an adsorption contactor having a solid adsorbent, particularly a polymeric amine adsorbent, more particularly a polymeric amine composite adsorbent, for separating components from a multi-component gas stream in an adsorption contactor. The adsorption contactor can include a plurality of adsorbent sheets or adsorbent configurations stacked or otherwise arranged adjacent to each other. In an embodiment, the adsorption contactor is a stack of a plurality of adsorbent sheets arranged on top of one another, wherein at least one channel is formed between two adjacent stacked adsorbent sheets or a pair of adsorbent sheets for allowing a fluid to flow through the at least one channel and thus through the contactor, wherein the fluid contacts the adsorbent sheet or adsorbent configuration. Each adsorbent sheet or adsorbent configuration can include a solid adsorbent, such as a polymeric amine adsorbent or a polymeric amine composite adsorbent, as described above. In an embodiment, at least 75% by weight of the adsorbent in the adsorbent sheet or adsorbent configuration comes from a polymeric amine adsorbent or a polymeric amine composite adsorbent, and the thickness of the adsorbent sheet or adsorbent configuration is in the range of about 0.1 mm to about 3 mm, or preferably about 0.2 mm to about 1 mm. In embodiments, the polymeric amine has greater than about 5 weight percent nitrogen from primary or secondary amine functional groups relative to the weight of the polymer. In embodiments, each adsorbent sheet or adsorbent configuration can have a molecular weight of about 0.2 g / cm 3 To about 0.8g / cm 3 Density within the range.
[0110] In an embodiment, the polymeric amine composite adsorbent can be formed by reacting a short (molecular weight less than 100 Daltons) vinyl amine monomer with a long (molecular weight greater than 100 Daltons) divinyl monomer to form a copolymer.
[0111] In an embodiment, the polymeric amine can be formed by reacting a water soluble polymeric amine having a molecular weight greater than 2000 Daltons with a long chain alkyl (8 carbons or more) ligand.
[0112] refer to Figure 1a , which shows an exemplary multiple adsorbent configuration or a set of two adsorbent sheets 12, which can include a polymeric amine adsorbent or a polymeric amine composite adsorbent, wherein multiple adsorbent sheets 12 are stacked adjacent to each other (or overlapped with each other) to form gaps or channels 14 therebetween for allowing fluid to flow through the channels 14 between the multiple sheets 12, 12 and contact each sheet 12, 12. Arrows 16 indicate the flow direction of the fluid (e.g., feed flow) in the channels 14. The adsorbent sheet 12 shown in the figure can be arranged in the form of a substantially flat plane, a flat sheet, or a planar configuration. The cross-section AA of the adsorbent sheet 12 is in Figure 1b1, shown as a sheet cross-section 20 (not shown to scale or aspect ratio relative to the adsorbent sheet 12), having an adsorbent configuration thickness or adsorbent sheet thickness 22. In alternative configurations, the adsorbent sheet or adsorbent configuration can have a thickness 22 and be non-planar. For example, the sheet can be corrugated to have alternative cross-sectional shapes, including, for example, Figure 1c The cross section of the square wave 30 shown, Figure 1d The bending wave or sine wave 31 cross section, such as Figure 1e The cross section of the triangle or triangular wave 32 shown in FIG. Figure 1f The sawtooth or sawtooth wave 32 cross section shown, or Figure 1g A cross section of a corrugated or corrugated shape 34 of a stack of alternating flat and corrugated sheets is shown. The thickness of an adsorbent configuration or adsorbent sheet can be calculated by dividing the volume by the area of the adsorbent configuration or adsorbent sheet. The size, shape and aspect ratio of the cross section can be selectively set to suit a particular application.
[0113] In an embodiment, the adsorption contactor can have a shell or a housing to substantially enclose a plurality of adsorbent sheets or adsorbent configurations and at least one channel. The shell or housing can have at least one inlet port and at least one outlet port, the inlet port being connected to at least one channel fluid for allowing a gas or fluid stream to enter the adsorption contactor, and the outlet port being connected to at least one channel fluid for recovering or discharging a product stream from the adsorption contactor. In an embodiment, the adsorption contactor can be provided with a plurality of adsorbent sheets or adsorbent configurations stacked on top of each other, thereby forming a repeatable stacking element having at least one channel between the adsorbent sheets or configurations. In an embodiment, there can be channels between the adsorbent sheets or configurations for multiple channels in the adsorption contactor. In an embodiment, the plurality of channels are substantially parallel to each other. In an embodiment, the plurality of channels may not be substantially parallel to each other.
[0114] In embodiments, the adsorption contactor can have one or more spacers for creating and / or maintaining at least one channel between adsorbent sheets or adsorbent configurations. The spacer can be a separate component disposed between each adsorbent sheet in a pair of adsorbent sheets. In embodiments, some adsorbent sheets or adsorbent configurations can have features or protrusions on them, or can have non-planar cross-sectional geometries or shapes, including, for example, Figures 1c to 1g As shown, the spacers may function in substantially the same manner as one or more spacers, that is, to create and / or maintain a spacing between each adsorbent sheet and at least one channel.
[0115] The protrusions can be made of a protrusion material that is substantially the same as the sorbent sheet or sorbent configuration material. For example, the sorbent sheet can be embossed.
[0116] The adsorption contactor can have one or more adsorbent sheets or adsorbent configurations, wherein the adsorbent sheet or adsorbent configuration can be formed or provided with at least one of a flat sheet, a pleated sheet, or a corrugated sheet.
[0117] A spacer that is a separate component and made of a different material than the adsorbent sheet or configuration can be attached to at least one adsorbent sheet or configuration, or arranged between adsorbent sheets or configurations when assembling the adsorbent contactor. The adsorbent contactor can include an adsorbent sheet or adsorbent configuration, wherein the spacer is printed on the adsorbent sheet or adsorbent configuration.
[0118] In embodiments, the adsorption contactor can have a channel voidage (one or more channels created by the adsorbent sheet or adsorbent configuration in the adsorbent contactor, also referred to as "channel voidage") ranging from about 20% to about 80% voidage, or preferably about 30% to about 75% voidage.
[0119] In an embodiment, the adsorbent sheet or adsorbent configuration contained in the adsorbent contactor disclosed herein includes a porous network geometry having a primary pore network of interconnected primary pores, which is also interconnected with a secondary pore network, wherein the average pore size of the primary pore network is about 1 micron to about 30 microns, and the average pore size of the secondary pore network ranges from about 10 nanometers to about 200 nanometers.
[0120] Such a pore structure can be obtained by forming an adsorbent sheet or adsorbent configuration from porous particles of the composition disclosed herein, the porous particles having an average particle size in the range of about 0.2 microns to about 40 microns.
[0121] During the fabrication of the adsorbent layer, imperfect packing of irregularly shaped particles can produce a pore network between the particles having primary pore sizes having an average diameter ranging from about 1 micron to about 30 microns.
[0122] This hierarchical structure of interconnected pores can facilitate rapid exchange of gases between adsorbent layers and process streams in channels between adsorbent layers or adsorbent configurations.
[0123] In an embodiment, the adsorption separator can include at least one adsorption contactor as described above. In a specific embodiment, the adsorption separator can have a housing or shell to substantially enclose at least one adsorption contactor or multiple adsorption contactors, the housing or shell having: at least one inlet port, the inlet port is fluidly connected to at least one channel of the adsorption contactor, for allowing a gas or fluid stream to enter the adsorption separator and the adsorption contactor; and at least one outlet port, the outlet port is fluidly connected to at least one channel of the adsorption contactor, for recovering or discharging a product stream from the adsorption contactor and the adsorption separator.
[0124] Embodiments of the present invention can include an adsorbent bed having a solid adsorbent, particularly a polymeric amine adsorbent, more particularly a polymeric amine composite adsorbent, for separating a multi-component gas stream. The adsorbent bed can include a container, an inlet port on the container, an outlet port on the container, and a plurality of adsorbent pellets, the adsorbent pellets including a solid adsorbent, such as a polymeric amine adsorbent or a polymeric amine composite adsorbent, as described herein. The polymeric amine adsorbent or the polymeric amine composite adsorbent can be disposed on and / or in an adsorbent support. The adsorbent bed can be a fixed bed or a fluidized bed.
[0125] How to use solid adsorbent
[0126] The solid adsorbents (e.g., polymeric amine adsorbents) or solid adsorbent components with different adsorbents and / or adsorption properties disclosed herein can be used to separate a first component (e.g., acid gas, carbon dioxide, nitrogen oxides and / or sulfur oxides) from a multi-component gas stream for reducing industrial or application harmful effluents, and for providing a concentrated stream of acid gas components (e.g., CO2), which can be further used for storage or other industrial purposes.
[0127] In embodiments, adsorbent separators, adsorbent beds and / or adsorbent contactors comprising polymeric amine adsorbents and / or polymeric amine composite adsorbents (having different adsorbents and adsorption properties) can be used in an adsorption process for separating a first component from a multi-component gas stream.
[0128] In an embodiment, an adsorptive gas separation method is provided for adsorptive gas separation of a multi-component fluid stream comprising at least a first component (the first component can include, for example, carbon dioxide, nitrogen oxides, and / or sulfur oxides) and a second component. In one such embodiment, the adsorption process can separate at least a portion of the first component from the multi-component fluid stream.
[0129] Figure 2 An embodiment of an adsorptive gas separation process 100 for separating a multi-component fluid stream including at least a first component and a second component is shown.
[0130] like Figure 2 As shown, initial step 101 includes providing an adsorption gas contactor having at least a polymeric amine adsorbent and / or a polymeric amine composite adsorbent as described herein. Method 100 employs an adsorption gas contactor comprising a plurality of adsorbent sheets or adsorbent configurations, as described herein, stacked on top of each other to create channels between each pair of adjacent stacked adsorbent sheets or adsorbent configurations, thereby creating one or more channels or channels for allowing fluid to flow through the contactor. In embodiments, a plurality of spacers can be arranged or otherwise positioned between each of the plurality of adsorbent sheets to create channels therebetween.
[0131] In an embodiment, the adsorption gas contactor can have a plurality of adsorbent sheets or configurations, each of the plurality of adsorbent sheets forming a channel with an adjacent adsorbent sheet. In an embodiment, each adsorbent sheet can have a polymeric amine adsorbent and / or a polymeric amine composite adsorbent as described above. In an embodiment, at least 75% by weight of the adsorbent on the adsorbent sheet or configuration is a polymeric amine adsorbent or a polymeric amine composite adsorbent. In some embodiments, the adsorbent sheet or configuration can have a thickness in the range of about 0.1 mm to about 3 mm, or preferably about 0.2 mm to about 1 mm, and about 0.2 g / cm 3 To about 0.8g / cm 3 The thickness of the adsorbent sheet is Figure 1b It is indicated as thickness 22 in FIG.
[0132] A multi-component gas stream (e.g., a combustion gas stream, a flue gas stream, a process gas stream, an acid gas stream, or an air stream) having at least a first component (e.g., carbon dioxide, sulfur oxides, or nitrogen oxides) and a second component (e.g., nitrogen) can be used as a feed stream and enter the contactor in the adsorption step 110. In an embodiment, the multi-component gas stream can also contain moisture. As the multi-component gas stream flows through the contactor, it contacts the polymeric amine adsorbent and / or the polymeric amine composite adsorbent, and at least a portion of the first component of the multi-component gas stream is adsorbed in and / or on the adsorbent. In an embodiment, the multi-component gas stream can enter and / or contact the polymeric amine adsorbent and / or the polymeric amine composite adsorbent at a pressure between about 1 bar absolute and about 2 bars absolute. In an embodiment, the feed stream can enter the contactor at a temperature between about 10° C. and about 90° C. Although not specifically shown, the remaining components of the multi-component stream or those components that are not adsorbed in and / or on the adsorbent material (e.g., the second component, such as nitrogen) flow through the contactor, exit from the contactor in the form of a first product stream, and are recovered.
[0133] In some embodiments, the polymeric amine adsorbent and / or polymeric amine complex adsorbent can be exposed to a first relative humidity, which can be equal to or greater than about 20% relative humidity (RH) during the adsorption step 110. In embodiments, the RH can be measured in the adsorbent sheet or configuration, particularly within the pore volume of the adsorbent sheet or configuration, when the gas in the pores and the adsorbent are approximately in thermal equilibrium.
[0134] Thermal equilibrium can be defined, for example, when the temperature of the gas in the pores and the temperature of the adsorbent are at a temperature difference equal to or less than about 2 degrees Kelvin.
[0135] In an embodiment, the polymeric amine adsorbent and / or the polymeric amine composite adsorbent and / or the contactor is at an adsorption temperature in the adsorption step 110. When or before the polymeric amine adsorbent or the polymeric amine composite adsorbent reaches a predetermined adsorption capacity, and / or when or before the first component in the first product stream breaks through, the adsorption step 110 can be terminated, and a subsequent step, such as a regeneration step 111, can be started.
[0136] In an embodiment, the first product stream is at least periodically depleted of the first component relative to the feed stream and further comprises a second component, such as nitrogen. In some embodiments, the first product stream is also enriched in the second component relative to the feed stream. In an embodiment, during the regeneration step, the first product stream is recovered from the contactor.
[0137] In the regeneration step 111, at least a portion of the first component adsorbed in and / or on the polymeric amine adsorbent and / or the polymeric amine composite adsorbent can be desorbed by at least one of a temperature swing mechanism and a partial pressure swing mechanism to form a second product stream. In an embodiment, in the regeneration step 111, the polymeric amine adsorbent and / or the polymeric amine composite adsorbent is exposed to and / or contacts a regeneration stream that increases the relative humidity in the contactor to a second relative humidity that is equal to or greater than the first relative humidity. In an embodiment, the second relative humidity is greater than the first relative humidity, or is about 20% relative humidity, as measured in the pores of the adsorbent, when the gas in the pores and the adsorbent are approximately in thermal equilibrium, for example, when the temperature of the gas in the pores and the temperature of the adsorbent are at a temperature difference equal to or less than about 2 degrees Kelvin.
[0138] In the regeneration step 111, the polymeric amine adsorbent and / or the polymeric amine composite adsorbent and / or the contactor can reach a regeneration temperature, wherein the regeneration temperature is greater than the adsorption temperature.
[0139] In an embodiment, a first regeneration stream including a third component (e.g., water or steam) can enter a contactor, be directed to contact a polymeric amine adsorbent and / or a polymeric amine composite adsorbent, and flow through the contactor. The first regeneration stream can be actively or passively controlled so that the partial pressure of the steam is equal to or greater than about 0.3 bar absolute pressure, and / or enter the contactor so that the partial pressure of the steam is equal to or greater than about 0.3 bar absolute pressure. As a result, at least a portion of the first regeneration stream or the third component can be adsorbed in and / or on the adsorbent, thereby generating heat of adsorption. The heat of adsorption is the result of a phase change experienced by the water, for example, from a gas phase (e.g., steam) to a liquid phase (e.g., liquid water), or to an adsorbed state on a solid surface (physical adsorption).
[0140] In an embodiment, the first regeneration stream comprises primarily steam. This is a preferred embodiment in applications and / or methods where it is desirable to separate and recover a product stream comprising a high purity first component (e.g., acid gas or CO2). In other embodiments, the first regeneration stream comprises a mixture of steam and a first component (e.g., an acid gas component, such as CO2).
[0141] In an embodiment, the regeneration stream is a steam stream having a pressure between 30 kPa and 120 kPa absolute and a temperature between 60°C and 110°C.
[0142] The structure formed by the porous thin sheet with porous solid adsorbent material (which is also stable to steam and liquid water) enables the rapid adsorption and desorption process to be used for the separation of CO2 from flue gas or other CO2-containing gases (including ambient air), i.e., direct air capture (DAC). Examples 5 and 11 are provided below to illustrate the demonstrated rapid adsorption / desorption kinetics capability. With a production rate greater than 10 TPD / T adsorbent, a large amount of CO2-containing gas is contacted with the solid adsorbent in a short period of time.
[0143] The typical contact time for the CO2-containing gas flowing through the structured contactor is less than 1 second, or less than 0.5 seconds, and more preferably less than 0.2 seconds. The high recovery rate of CO2 indicates that most adsorbent materials can access the imported CO2 within a fraction of a second. The present invention combines the benefits of the structured adsorbent design disclosed in PCT patent application WO2021 / 240476A1 with the benefits of customized amine-based adsorbent powders to enable CO2 capture at low CO2 concentrations (less than 10% CO2) (in air (DAC), as low as 400 ppm CO2), while using a rapid regeneration steam addition step to provide an extended life for the solid adsorbent in applications.
[0144] In an embodiment, the capture cycle time is less than 120 seconds, preferably less than 60 seconds, and more preferably less than 40 seconds.
[0145] In an embodiment, the adsorption heat generated by the adsorption of water on the polymeric amine adsorbent and / or the polymeric amine composite adsorbent can be used as at least a portion of the desorption heat, which is used to desorb at least a portion of the first component adsorbed in the adsorbent and / or on the adsorbent. The desorbed first component together with other components in the gas phase can form a second product stream. Therefore, in some embodiments, the second product stream can be at least periodically enriched in the first component relative to the feed stream. That is, the concentration of the first component desorbed from the adsorbent material in the second product stream can be greater than the concentration of the first component in the multi-component stream. The second product stream can then be discharged or recovered from the contactor.
[0146] In embodiments, in an adsorptive gas separation process using a contactor comprising a polymeric amine adsorbent and / or a polymeric amine composite adsorbent as disclosed herein, wherein steam is used as the regeneration stream, and / or in an adsorptive gas separation process in which water is capable of being adsorbed on and / or in an adsorbent sheet, leaching or evaporation of amines from the adsorbent and / or adsorbent sheet will be reduced or substantially eliminated.
[0147] In an embodiment, in the regeneration step 111, at least a portion of the first component adsorbed in and / or on the polymeric amine adsorbent and / or the polymeric amine composite adsorbent can be desorbed by a pressure swing mechanism, or a combination of a pressure swing mechanism and a temperature swing mechanism, and / or a partial pressure swing mechanism.
[0148] In an embodiment, in the conditioning step 112, a component (e.g., a third component, such as water) adsorbed on and / or in the polymeric amine adsorbent and / or the polymeric amine composite adsorbent can be desorbed from the adsorbent by at least one of a temperature swing mechanism and a partial pressure swing mechanism to form a third product stream. In a preferred embodiment, in the conditioning step 112, the polymeric amine adsorbent and / or the polymeric amine composite adsorbent is subjected to or exposed to a third relative humidity, wherein the third relative humidity is less than the second relative humidity. By introducing the conditioning stream into the adsorbent contactor, the adsorbent is exposed to a swinging or reduced relative humidity in the conditioning step 112 relative to the regeneration step 111, resulting in the adsorbed moisture on and / or in the adsorbent being desorbed, and the moisture can again form at least a portion of the third product stream. In an embodiment, the conditioning stream enters the contactor, and then the conditioning stream contacts the polymeric amine adsorbent and / or the polymeric amine composite adsorbent in the contactor, and the conditioning stream has a third relative humidity, wherein the third relative humidity is less than the second relative humidity. The conditioning stream can be, for example, at least one of an air stream, an inert gas stream, and / or a nitrogen stream. Thus, in some embodiments, the third product stream can be at least periodically enriched in the third component relative to the conditioning stream.The component desorbed from the adsorbent in the conditioning step 112 can form a third product stream that can be discharged or recovered from the contactor.
[0149] In other embodiments, desorption of the third component or water adsorbed on and / or in the adsorbent can be performed or assisted by applying a vacuum and reducing the pressure within the contactor to a pressure below the saturation pressure of the third component, steam or water within the contactor.
[0150] Additional optional next steps ( Figure 2 110) can be followed by, for example, a cooling step, wherein the temperature of the polymeric amine adsorbent and / or polymeric amine composite adsorbent can be reduced prior to repeating the adsorption step 110. The cycle of the adsorption step 110, the regeneration step 111, the optional conditioning step 112 (and optional subsequent steps) can be repeated as needed.
[0151] In an embodiment, an adsorptive gas separation method for separating at least a first component from a multi-component gas stream can include: providing a contactor as described herein; allowing the multi-component gas stream to enter the adsorbent contactor as a feed stream through an inlet port; allowing at least a portion of the first component from the feed stream to be adsorbed on a polymeric amine adsorbent; recovering a first product stream from the adsorbent contactor through an outlet port, the first product stream being at least periodically enriched with a second component relative to the feed stream; allowing a first regeneration stream to enter the adsorbent contactor, the first regeneration stream selectively having a steam content greater than 80% (molar fraction) purity and a steam partial pressure equal to or greater than about 0.3 bar absolute pressure; allowing steam or water to be adsorbed on the polymeric amine adsorbent and / or the polymeric amine composite adsorbent, and selectively generating heat of adsorption or heat of condensation , optionally, wherein the energy released when water is adsorbed onto the adsorbent is greater than the energy required to desorb the first component from the polymeric amine adsorbent and / or the polymeric amine composite adsorbent; desorbing at least a portion of the first component adsorbed on the adsorbent and forming a second product stream that is at least periodically enriched in the first component relative to the feed stream; recovering the second product stream from the adsorbent contactor; and selectively desorbing water adsorbed on the adsorbent by entering a conditioning stream (e.g., an air stream, an inert gas stream, and / or a nitrogen stream) having a third relative humidity (wherein the third relative humidity is less than the second relative humidity), and / or by applying a vacuum and reducing the pressure within the contactor to a pressure below the saturation pressure of at least one of the third component, steam, and / or water in the contactor.
[0152] In adsorptive gas separation processes, particularly adsorptive gas separation processes using steam in the regeneration stream during the regeneration step and / or adsorptive gas separation processes in which water can be adsorbed on and / or in the adsorbent sheets, the use of polymeric amine adsorbents and / or polymeric amine composite adsorbents as described above provides the advantage of reducing leaching or evaporation of amines from the adsorbent, thereby resulting in increased durability of the adsorbent and contactor.
[0153] Example
[0154] Example 1A: Supported Amine Polymer
[0155] Preparation of PEIDS
[0156] High pore volume silica [1.2 ml / g] was mixed at 20°C with a PEI polymer (10K Daltons) that had been functionalized by reaction with 12-epoxy-dodecane (ED) in isopropanol for 1 hour. Prior to the addition of silica, additional inorganic antioxidant salts dispersed in water were added at 1.6% weight fraction of the dry adsorbent powder dissolved in water, resulting in an IPA / water mixed solvent mass ratio of 9 / 1. Finally, the high pore volume silica was slowly mixed into the solution so as to achieve the following mass ratio PEI / ED / SiO2 of 85 / 51 / 100 in the dry powder. The formed slurry was stirred for another 20 hours at room temperature. The solvent was then removed in a rotary evaporator at 60°C. The recovered powder was placed in a drying oven at 100°C for 1 hour. The recovered powder was then tested for CO2 capacity using a TGA instrument, and the measured CO2 adsorption capacity of the powder was 44±2 cc / g CO2 using 10% CO2 in a balanced nitrogen supply at 50°C.
[0157] Example 1B: Adsorbent Sheet Preparation
[0158] The powder of Example 1A was mixed with water and a polymer binder and dispersant in a water / powder / binder / dispersant weight ratio of 64.8 / 32 / 2.5 / 0.7. The binder was a styrene acrylic binder added to the slurry as a 45 wt% solution and the dispersant was a mixture of a defoamer and a surfactant to stabilize the suspension.
[0159] The suspension was placed in a high shear mixer for 1 hour and then placed in a ball mill drum with stabilized zirconium oxide grinding balls and rotated for 24 hours. The slurry was then distributed to a slot die coater apparatus equipped with a nonwoven (NW) carbon substrate (17 g / m 2, thickness of 0.2mm), operated at 2m / min. During the coating process, the slurry temperature was maintained between 20°C and 25°C as the slurry impregnated the NW carbon substrate. The slurry pump speed was adjusted to limit the outer coating and slurry removal with a scraper downstream of the slot die slurry injection and before the sheet was dried. Local drying of the coated sheet was completed between the coating station and the collection roller, and the travel time was between two 3-minute passes through the forced air convection oven section, which was set to 60°C. The collected sheets were further dried in the oven at 100°C for 1 hour and stored at room temperature awaiting further processing. The resulting sheet had a thickness of 0.275±0.015mm and an average density of 0.59g / ml and a CO2 adsorption capacity of 38±2cc / g at 50°C using 10% CO2 in a balanced nitrogen supply.
[0160] Embodiment 2:
[0161] Figure 3a , 3b 3c and 3d show scanning electron microscope (SEM) images of a sheet of polyethyleneimine supported on porous silica from Example 1B and impregnated on a NW carbon film substrate. Figure 3a and 3b , while the cross-sectional view is shown in Figure 3c Indicated in.
[0162] exist Figure 3a In the images, large-scale features such as cracks in the adsorbent film at the sheet surface and adsorbent-coated carbon fibers protruding from the membrane surface can be observed. Figure 3b An enlarged portion of the surface film of the adsorbent sheet is shown, illustrating the porous structure of the denser areas. Figure 3c A cross-section of an adsorbent sheet is shown, with a distribution of interconnected small and large pores to facilitate rapid transport of fluid components within the adsorbent sheet.
[0163] Embodiment 3:
[0164] A sample of the adsorbent sheet from Example 2 was placed in a thermogravimetric apparatus (TGA), dried, and conditioned by contacting the sample with nitrogen while holding the sample at 100°C for 1 hour to remove any CO2 adsorbed due to exposure to air and moisture. The sample was then cooled to 50°C in nitrogen and the fluid flow was switched to 10% CO2 in a balance nitrogen flow. The increase in sample weight was recorded and converted to adsorption capacity per gram of sample after an equilibrium plateau was obtained. The measured capacity of the sheet for CO2 at 50°C under an atmosphere of 10% CO2 in nitrogen was 38±2cc / g. For reference, the CO2 adsorption capacity of the adsorbent powder itself under the same test conditions was 45±2cc / g.
[0165] Example 4: (0 = "fail"; 1 = "pass") Water stability test.
[0166]
[0167]
[0168] Pass / Fail Cold Water Stability Test: 0.2 g powder in 10 g 20°C DI water, mixed for 1 hour. Liquid filtered off and powder dried before testing. CO2 adsorption capacity was tested on a set of samples prepared to have the same molar ratio of nitrogen in PEI / alkylene oxide and weight ratio of silica to amine polymer as Example 1. "0" indicates a loss of CO2 capacity greater than 5%. "1" indicates no detectable loss (within 1 cc / g CO2 capacity or 2% measurement error). Each row corresponds to a different polymer molecular weight and each column corresponds to the number of carbons in the alkyl chain in the alkylene oxide used for PEI functionalization. Water Exposure Stability Table.
[0169] Embodiment 5:
[0170] The adsorbent sheet from Example 2 was placed on a flat screen printer to deposit epoxy resin dot areas of 1.6 mm diameter and 0.3 ± 0.015 mm height, which were then thermally cured (epoxy resin crosslinked) in air at 100° C. for 1 hour. Strips 1.2 m long and 1 inch wide were cut and stacked to form a structured adsorbent bed encapsulated in a 1.6 mm thick polymer (ULTEM) board for loading into a test device for conveying a synthetic supply of CO2 flue gas, steam and nitrogen and for recycling a CO2-depleted synthetic flue gas, a purified CO2 stream and a humid nitrogen stream.
[0171] The synthetic supply stream (0% CO2, 3% H2O, balance N2) has a pressure between 105 kPa and 115 kPa absolute and a temperature of 40±2°C, the steam stream has a pressure between 90 kPa and 100 kPa and a temperature of 110±5°C (superheated), and the nitrogen stream has a pressure between 105 kPa and 115 kPa, which is divided into two streams at temperatures of 110±5°C and 80±5°C.
[0172] The bed samples were placed in a temperature controlled jacket set at 80°C to minimize the effects of heat losses through the sides of the bed and to better represent the performance of a larger bed operating with negligible parasitic heat losses through the sides of the bed.
[0173] Rapid cycling between these four feed streams results in the purification of CO2. The duration and flow rate of each addition are adjusted until a satisfactory CO2 capture efficiency and CO2 product purity is obtained. Typically, the cycle length is between 40 and 90 seconds.
[0174] Test 1 Test 2 Cycle time (seconds) 68 50 <![CDATA[Volume productivity (TPD / m 3 )]]> 10.2 14.1 Weight productivity (TPD / T) 46.2 64 <![CDATA[CO2 recovery]]> 84% 81% <![CDATA[CO2 purity]]> 86.50% 85.50%
[0175] Productivity is defined as tons of CO2 purified per cubic meter of structured bed volume per day (TPD / m3) or per ton of structured bed (TPD / t). CO2 recovery is defined as the fraction of CO2 in the product stream divided by the amount of CO2 introduced into the adsorption bed with the feed. CO2 purity refers to the product stream after water has been removed.
[0176] Example 6A:
[0177] The sequential aggregation can be seen in Scheme 1 below.
[0178] (1) Salt formation
[0179]
[0180] A 250ml round-bottomed three-necked glass flask equipped with a condenser, nitrogen inlet and outlet, and a Teflon-coated stirring rod is used for the reaction. The flask is flushed with nitrogen and immersed in an ice bath. Then it is loaded with 40g isopropanol and 18g hydrochloric acid (36-37% concentration). When the mixture is subsequently cooled to a temperature lower than 10°C, 10g of 98% purity of allylamine is added dropwise while stirring, and the temperature remains lower than 20°C during this period. Then, 0.5g DVB and 1.3g V-50 are added, and the temperature is increased to 55°C. Then, other 1.5g DVB aliquots are added to the flask in 3 separate batches at 1 hour, 2 hours, and 3 hours. Then, the reaction temperature is increased to 65°C, and is kept at this temperature for another 3 hours. Then, the product is diluted with 20g methanol and filtered with a Buchner funnel. Then, the solid portion of the mixture is suspended in 40g DI water, and 8g NaOH is added under stirring. After 30 minutes, the solid was filtered and washed twice with DI water. It was then further washed with methanol. The powder was then dried overnight in a vacuum oven at 60°C. The post-treatment of the solid powder was the same as in Example 1. A yield of 20% was obtained, and the CO2 capacity measured at 50°C with a flowing gas of 10% CO2 and 90% He was 36.8cc / g resin. Then, 4g of DVB-80 (DVBAldritch) comonomer and 0.85g of 22'-azobis(2-amidinopropane) dihydrochloride (V-50) initiator were added, and the temperature was raised to 55°C and maintained at this temperature for 18 hours under stirring. The product was then diluted with 20g of methanol and filtered with a Buchner funnel. The solid portion was then suspended in 40g of DI water, and 8g of NaOH was added under stirring. After 30 minutes, the solid was filtered and washed twice with DI water. It was further washed with methanol. The resulting powder was then dried in a vacuum oven at 60°C overnight.
[0181]
[0182] Example 6B:
[0183] The reaction was carried out in a 500 ml round bottom three neck glass flask equipped with mechanical stirring of a polytetrafluoroethylene coated shaft and blades, nitrogen inlet and outlet and a thermometer. The flask was immersed in an ice bath and purged with nitrogen, then loaded with 165 g HCl (36-37%) and 1.65 g NaCl. The mixture was then cooled to a temperature of about 15° C., 110 g of allylamine was slowly added under stirring, during which the temperature remained below 30° C. After cooling to 15-20° C., 17.5 g of citric acid was slowly added, and the resulting pH measurement was 5.5. Then, 18 g of V-50 and 6 g of DVB were added, and the temperature was raised to 65° C. 44 g of DVB was added by a syringe pump in 4.3 hours, during which the temperature was maintained between 67-70° C. After the addition of DVB, the reaction continued for another 2.5 hours with the temperature raised to 82° C. The post-treatment of the solid powder was the same as in Example 14 below. A yield of 46.3% was obtained and the CO2 capacity was 46.9 cc / g resin at 50°C with a flowing gas of 10% CO2 and 90% He. Figure 4 It is a broad unimodal distribution curve with a peak at about 4 μm and a tail at 70 μm. Scanning electron microscopy (SEM) images show that the solid polymer mainly consists of aggregates of nanoparticles.
[0184] Example 6C:
[0185] The polymerization was repeated three times on a larger scale in a 5L round-bottom three-necked glass flask equipped with a mechanical stirrer of a Teflon coated shaft and blades. The flask was purged with nitrogen and charged with 1004g of a cold (approximately 8-10°C) dilute aqueous HCl solution containing 68g of allylamine, 6.6g of NaCl and 96g of citric acid. The pH of the reaction solution was about 6. Then, 72g of V-50 and 24g of DVB were added, and the temperature was raised to 65°C. Then, 176g of DVB was added by a syringe pump over a period of 4.25 hours, during which the temperature was maintained between 67 and 70°C, and 640g of water was added for dilution as the viscosity increased. After the addition of DVB, the reaction continued for another 1.5 hours, while the temperature was raised to 80°C.
[0186]
[0187] CO2 adsorption capacity at 10% CO2 in He at 50 °C for replicate scaled-up samples.
[0188] Example# batch C (wt%) H (wt%) N (wt%) S (wt%) 6c-1 #180619 72.99 11.73 7.37 0.82 6c-2 #180626 73.01 13.49 7.09 1.08 6c-3 #180703 68.80 12.49 8.02 0.61
[0189] Composition of dried polymer from elemental analysis.
[0190] Embodiment 7:
[0191] Representative samples of the allylamine co-DVB polymers provided herein as well as a reference commercially available amine-doped resin containing aniline (Lewatit 1065) were subjected to repeated cycles of exposure to air for 1 hour at 120° C. The CO 2 capacity of the material was measured at 50° C. between each cycle.
[0192] Figure 5a The CO2 capacity of the samples after 1 and 20 air exposure cycles are compared. The CO2 capacity per gram of adsorbent at 10% CO2 in N2 at 50°C is represented on the y-axis, while the amine-doped resin (Lewatit 1065) adsorbent containing aniline and the allylamine co-DVB polymer adsorbent are represented along the x-axis. The unshaded bars represent the CO2 capacity after 1 cycle, while the shaded bars represent the CO2 capacity after 20 cycles. The volume of CO2 adsorbed is reported at STP (standard temperature and pressure).
[0193] Figure 5b The CO2 adsorption capacity of a reference amine-containing resin (Lewatit 1065) and a porous polymer disclosed herein before and after water soaking is shown. The CO2 capacity per gram of adsorbent at 10% CO2 in N2 at 50°C is shown on the y-axis, while the amine-doped resin (Lewatit 1065) adsorbent containing aniline and allylamine co-DVB polymer adsorbents 180420, 180423, and 180425 are shown along the x-axis. The unshaded bars represent the CO2 capacity before soaking, while the shaded bars show the CO2 capacity after soaking. The volume of CO2 adsorbed is reported at STP.
[0194] Two of the prepared porous amine adsorbent samples showed no loss of CO 2 capacity and excellent adsorption capacity compared to the reference, indicating that the amine monomers were effectively contained in the porous copolymer while leaving little unreacted monomers in the solid adsorbent.
[0195] The sample from Example 6A is significantly more oxidatively stable than the reference amine resin material.Hot water stability was tested by comparing the CO2 capability of the resin before and after the powder was soaked for 1 hour under mixing.
[0196] Embodiment 8:
[0197] Preparation of adsorbent sheets:
[0198] 164 g of the sample of Example 6C before drying (containing 81% dry polymer) was mixed with 300 g of water and 54 g (43% wt suspension) of polyvinyl alcohol polymer (molecular weight of about 200K Daltons) in a high shear mixer for 1 hour, then transferred to a ball mill container with zirconium oxide stabilizing beads and rotated for 24 hours. The slurry was then dispensed onto a NW carbon substrate (17 g / m2 , thickness 0.2mm) in a slot die coater device operated at 2m / min. As the slurry impregnates the NW carbon substrate, the slurry temperature is maintained between 20°C and 25°C during the coating process. The slurry pump speed is adjusted to limit the removal of the outer coating and slurry by a scraper downstream of the slot die slurry injection before the sheet dries. Partial drying of the coated sheet occurs between the coating station and the collection roller as the sheet travels partially through a forced air convection oven set to 60°C for 3 minutes. The collected sheets are further dried in an oven at 100°C for 1 hour and stored at room temperature until further processing. The resulting sheet has a thickness of 0.18±0.01mm and an average density of 0.47g / ml and a CO2 adsorption capacity of 30±2cc / g at 50°C in 10% CO2 and balanced nitrogen supply.
[0199] Embodiment 9:
[0200] Figure 6a shows a powder scanning electron microscope (SEM) image of Example 6B, Figure 6b The cross-sectional SEM image of the adsorbent sheet of Example 8 is shown. Figure 6a Submicrometer-diameter polymer particles were observed in Figure 6b A porous network with pores in the micrometer size range can be observed in the Figure 1 (dark areas). The interstitial spaces between the polymer particles remain upon coating.
[0201] Figure 6b is a powder SEM image of a cross section of an adsorbent sheet from Example 8, showing the polymer particles and porosity of the adsorbent film. The darker areas are the voids that remain between the adsorbent particles after forming the adsorbent sheet. These voids or pores are interconnected in a three-dimensional network and enable rapid diffusion and transport of fluid or gas components to the surface of individual adsorbent particles.
[0202] Embodiment 10:
[0203] A sample of the adsorbent sheet from Example 9 was placed in a thermogravimetric apparatus (TGA), dried and conditioned by contacting the sample with nitrogen while holding the sample at 140°C for 20 minutes to remove any CO2 and moisture adsorbed due to exposure to air. The sample was then cooled to 50°C in nitrogen and the fluid flow was switched to 10% CO2 in a balance nitrogen flow. The increase in sample weight was then recorded and converted to adsorption capacity per gram of sample once an equilibrium plateau was obtained. The measured capacity of the sheet for CO2 at 50°C was 30±2cc / g in an atmosphere of 10% CO2 in balance nitrogen. For reference, the CO2 adsorption capacity of the adsorbent powder itself under the same test conditions was 35±2cc / g. Figure 7The mass change of the adsorbent sheet sample during the TGA test is shown, where the sample weight is on the right axis vs. time and the temperature near the sample is on the left axis. The sample was first exposed to nitrogen at 140°C for 20 minutes to dry the material and remove the CO2 adsorbed by exposure to air.
[0204] The gas composition in the TGA furnace was switched to 10% CO2 in N2 at the 51 minute mark. An 80% increase in sample sheet weight was observed in less than 2 minutes, indicating rapid adsorption of CO2 in the adsorbent sheet. The 6% mass change of the sample 20 minutes after the introduction of CO2 corresponds to an adsorption capacity of approximately 30 cc / g STP.
[0205] Embodiment 11:
[0206] The adsorbent sheet from Example 10 was arranged on a flat screen printer to deposit epoxy resin dot areas of 1.6 mm diameter and 0.25±0.01 mm height, which were then thermally cured (crosslinking of the epoxy resin) in air at 100° C. for 1 hour. Strips 1.2 m long and 1 inch wide were cut and stacked to form a structured adsorbent bed encapsulated in a 1.6 mm thick ULTEM board for loading into a test device for conveying a synthetic supply of CO2 flue gas, steam and nitrogen and for recycling a CO2-depleted synthetic flue gas, a purified CO2 stream and a humid nitrogen stream.
[0207] The synthetic supply stream (10% CO2, 3% H2O, balance nitrogen) has a pressure between 105 kPa and 115 kPa absolute and a temperature of 40±2°C, the steam stream has a pressure between 90 kPa and 100 kPa and a temperature of 110±5°C (superheated), the nitrogen stream has a pressure between 105 kPa and 115 kPa, and is divided into two streams at temperatures of 110°C±5°C and 80°C±5°C.
[0208] The bed samples were placed in a temperature controlled jacket set at 80°C to minimize the effects of heat losses through the sides of the bed and to better represent the performance of larger beds operated with negligible parasitic heat losses through the sides of the bed.
[0209] Rapid cycling between these four feed streams results in purification of the CO2. The duration and flow rate of each addition is adjusted until a satisfactory CO2 capture efficiency and CO2 product purity is obtained. Typical cycle lengths are between 40 and 120 seconds.
[0210] Test 1 Test 2 Cycle time 123 109 <![CDATA[Throughput per unit volume (TPD / m 3 )]]> 3 3.3 Weight productivity (TPD / T) 22.6 24.8 <![CDATA[CO2 Recovery]]> 60% 40% <![CDATA[CO2 purity]]> 80% 78%
[0211] Productivity is defined as tons of CO2 purified per cubic meter of structured bed volume or per ton of structured bed per day. CO2 recovery is defined as the fraction of CO2 in the product stream divided by the amount of CO2 introduced into the adsorption bed with the feed. CO2 purity refers to the product stream after water has been removed.
[0212] The exemplary embodiments described herein are not intended to be exhaustive or to limit the scope of the invention to the precise forms disclosed. They are selected and described to explain the principles of the invention and its application and practical use, so as to allow others skilled in the art to understand its teachings.
[0213] According to the foregoing disclosure, it is apparent to those skilled in the art that, without departing from the scope of the present invention (comprising the combination of various described embodiments or their parts), many changes and modifications can be made in the practice of the present invention. Therefore, the scope of the present invention should be interpreted according to the content defined by the claims.
Claims
1. A solid adsorbent comprising: A polymeric amine having an average molecular weight greater than 2000 Daltons, wherein the solid adsorbent is insoluble in water and forms a porous network, and The solid adsorbent is in the form of particles, films or sheets.
2. The solid adsorbent according to claim 1, wherein: The polymeric amine comprises a first soluble domain and a second insoluble domain.
3. The solid adsorbent according to claim 1 or 2, wherein: The polymeric amine comprises a primary amine and a secondary amine, and the mass fraction of the combination of the primary amine and the secondary amine relative to the mass of the polymeric amine is greater than 6 mass percent nitrogen.
4. The solid adsorbent according to claim 3, wherein: The polymeric amine also includes a tertiary amine having a mole fraction that is less than 20 mole percent of the nitrogen in the polymeric amine.
5. The solid adsorbent according to any one of claims 1 to 4, wherein: The average pore volume of the solid adsorbent is greater than 0.2 ml / g.
6. The solid adsorbent according to claim 5, wherein: The average pore volume of the solid adsorbent is in the range of 0.3 ml / g to 1.5 ml / g.
7. The solid adsorbent according to any one of claims 1 to 6, wherein: The average BET surface area of the solid adsorbent is 4 m 2 / g-500m 2 / g range.
8. The solid adsorbent according to claim 7, wherein: The average BET surface area of the solid adsorbent is 20 m 2 / g-300m 2 / g range.
9. The solid adsorbent according to any one of claims 1 to 8, wherein: The solid adsorbent has an average pore size in the range of 10 nm to 200 nm, the average pore size being measured using a nitrogen adsorption isotherm.
10. The solid adsorbent according to any one of claims 1 to 9, wherein: When the solid adsorbent is in the form of particles, the average particle size of the particles is in the range of 0.2 microns to 40 microns.
11. The solid adsorbent according to any one of claims 1 to 10, wherein: The polymeric amines include copolymers formed by the reaction of vinyl amine and divinyl monomers, and also include interconnected porous structures.
12. The solid adsorbent according to any one of claims 1 to 10, wherein: The polymeric amines include copolymers of allylamine and divinylbenzene (DVB).
13. The solid adsorbent according to any one of claims 1 to 10, wherein: The polymeric amines include copolymers of ethyleneimine and divinylbenzene (DVB).
14. The solid adsorbent according to any one of claims 1 to 10, wherein: The polymeric amine is supported on a porous support.
15. The solid adsorbent according to claim 14, wherein: The porous support is insoluble in water.
16. The solid adsorbent according to claim 14, wherein: The polymeric amines include polyethyleneimines functionalized with C10-C16 alkyl alcohols.
17. The solid adsorbent according to claim 16, wherein: The porous support is insoluble in water.
18. The solid adsorbent according to any one of claims 12 to 15, wherein: The porous support is a porous inorganic solid support having a pore volume in the range of 0.3 ml / g to 1.5 ml / g.
19. The solid adsorbent according to claim 18, wherein: The porous support is a porous inorganic solid support having a pore volume in the range of 0.7 ml / g to 1.5 ml / g.
20. The solid adsorbent according to claim 16, wherein: The molar ratio of long chain alkane groups to amine groups is in the range of 10% to 25%.
21. The solid adsorbent according to claim 16, wherein: The polyethyleneimine is functionalized by reaction with an alkyl epoxide.
22. The solid adsorbent according to any one of claims 1 to 21, wherein: The solid adsorbent is in the form of a self-supporting sheet or adsorbent configuration having a thickness in the range of 0.1 mm to 3 mm.
23. The solid adsorbent according to claim 22, wherein: The self-supporting sheet or the adsorbent configuration also includes a porous network structure, which has a primary pore network and a secondary pore network interconnected with each other, wherein the primary pore network has primary pores with an average diameter greater than 1 micron but less than 30 microns, and the secondary pore network has secondary pore diameters with an average diameter in the range of 10-200 nanometers.
24. The solid adsorbent according to any one of claims 1 to 23, further comprising: A porous supporting sheet for supporting the solid adsorbent.
25. The solid adsorbent according to any one of claims 1 to 24, wherein: The solid adsorbent has a ratio of CO2 equilibrium capacity to heat capacity between 15-40 cc STP CO2 / (J / K) per unit heat capacity of the solid adsorbent, wherein the equilibrium capacity is measured at 50°C at a 15% CO2 feed mixture.
26. A solid adsorbent comprising: A polymeric amine that forms a porous solid, the polymeric amine being characterized by: (a) a CO2 equilibrium capacity, wherein the ratio of the CO2 equilibrium capacity to the heat capacity of the solid adsorbent is between 15-40 cc STPCO2 / (J / K) per unit heat capacity of the solid adsorbent, wherein the equilibrium capacity is measured at 50°C with a 15% CO2 feed mixture; (b) a kinetic adsorption rate, wherein the kinetic adsorption rate is greater than 0.03 mmol / g / s when contacted with a CO2 mixture comprising 15% CO2 and at a temperature between 30°C and 50°C; (c) heat of adsorption of CO2, wherein the heat of adsorption of CO2 is between 70-120 kJ / mol of adsorbed CO2.
27. The solid adsorbent according to claim 26, wherein: The solid adsorbent is further characterized in that the adsorption capacity decreases by less than 10% of the adsorption capacity after 50,000 operating cycles, in which the solid adsorbent is exposed to a regeneration step, the regeneration step being at a temperature in the range between 90° C. and 130° C. and a relative humidity in the range of 50% to 100%.
28. The solid adsorbent according to claim 26 or 28, wherein: The polymeric amine is a copolymer of vinylamine and a divinyl monomer having primary and / or secondary amine groups, and an interconnected porous structure.
29. The solid adsorbent according to claim 26, wherein: The polymeric amine also includes a crosslinking agent comprising a copolymer of propylene imine and divinyl benzene.
30. The solid adsorbent according to claim 28, wherein: The copolymer of vinylamine and divinyl monomer is a copolymer of ethyleneimine and divinylbenzene.
31. The solid adsorbent of claim 26, wherein: The polymeric amine also includes a grafted alkyl amine supported on a porous support, the porous support having a pore volume in the range of 0.7 ml / g to 1.5 ml / g, and the grafted functional groups on the amine groups include hydrophobic groups.
32. The solid adsorbent according to any one of claims 26 to 31, wherein: The polymeric amine is a polyethyleneimine functionalized with a C10-C16 alkyl alcohol supported on a porous organic solid support or a porous inorganic solid support.
33. The solid adsorbent of claim 32, wherein: The polyethyleneimine is functionalized by reaction with an alkyl-epoxide at subambient temperature.
34. An adsorption gas contactor comprising: A plurality of adsorbent sheets, each of which comprises the solid adsorbent according to any one of claims 1 to 33, wherein the thickness of the adsorbent sheet is in the range of 0.1 mm to 3 mm, or preferably in the range of 0.2 mm to 1 mm, and is positioned to form channels between the plurality of adsorbent sheets so that a gas flow can flow between the adsorbent sheets and contact the adsorbent sheets.
35. An adsorption gas contactor comprising: a plurality of adsorbent sheets, each of the plurality of adsorbent sheets comprising a solid adsorbent, each of the adsorbent sheets having a thickness in the range of 0.1 mm to 3 mm, and positioned to form a channel between the plurality of adsorbent sheets so that a gas flow can flow between the adsorbent sheets and contact the adsorbent sheets, and Wherein, the density of the solid adsorbent sheet is 0.2g / cm 3 -0.8g / cm 3 and include polymeric amine polymers having greater than 5 weight percent nitrogen from primary or secondary amine functional groups, the polymeric amine being formed as a copolymer from a vinylamine monomer having a molecular weight less than 100 Daltons and a divinyl monomer having a molecular weight greater than 100 Daltons, or being formed by the reaction of a water soluble polymeric amine with a long chain alkyl (8 or more carbon) group.
36. The adsorptive gas contactor of claim 35, wherein: The solid adsorbent comprises adsorbent particles, and the average particle size of the adsorbent particles is in the range of 0.2-40 microns.
37. The adsorptive gas contactor of claim 35 or 36, wherein: The adsorbent sheet is embossed and / or has protrusions for forming the channels between the plurality of stacked adsorbent sheets.
38. The adsorptive gas contactor of claim 35, 36 or 37, wherein: At least some of the plurality of stacked adsorbent sheets have non-planar cross-sections for creating the channels between the plurality of stacked adsorbent sheets, wherein the non-planar cross-sections are wavy, sinusoidal, square, triangular or sawtooth cross-sections.
39. The adsorptive gas contactor of claim 35 or 36, further comprising: There is a channel void ratio between the plurality of adsorbent sheets, wherein the channel void ratio is in the range of 20%-80%, or preferably in the range of 30%-75%.
40. The adsorptive gas contactor of any one of claims 35 to 39, wherein: The thickness of each of the plurality of adsorption sheets is in the range of 0.2 mm to 1 mm.
41. An adsorptive gas separation process for separating a first component from a multi-component fluid stream comprising at least a first component and a second component, the process comprising: (a) providing an adsorption gas contactor, the adsorption gas contactor comprising the solid adsorbent according to any one of claims 1 to 33; (b) passing the multi-component fluid stream through the adsorptive gas contactor, adsorbing at least a portion of the first component from the multi-component fluid stream on the solid adsorbent to form a first product stream, and recovering the first product stream from the adsorptive gas contactor, wherein the first product stream is reduced in the first component relative to the multi-component fluid stream; and (c) desorbing at least a portion of the first component adsorbed on the solid adsorbent to form a second product stream, and recovering the second product stream from the adsorptive gas contactor, wherein the second product stream is enriched in the first component relative to the multi-component fluid stream.
42. The adsorptive gas separation method of claim 41, wherein: The adsorption gas contactor is the adsorption gas contactor according to any one of claims 35 to 39.
43. The adsorptive gas separation method according to claim 41 or 42, further comprising: The solid adsorbent is exposed to a first relative humidity in step (b), wherein the first relative humidity is a relative humidity of at least 20% measured at the inlet of the adsorption gas contactor.
44. The adsorptive gas separation method of claim 43, further comprising: In step (c), the solid adsorbent is exposed to a second relative humidity, wherein the second relative humidity is greater than the first relative humidity.
45. The adsorption gas separation method according to any one of claims 41 to 44, wherein: In step (b), the adsorption is performed at a first temperature, and in step (c), the desorption is performed at a second temperature, the second temperature being greater than the first temperature.
46. The adsorption gas separation method according to any one of claims 41 to 45, further comprising: In step (c), a regeneration stream is passed to the adsorption gas contactor, the regeneration stream comprising steam or consisting essentially of steam.
47. The adsorptive gas separation method of claim 41, further comprising: In step (c), before the regeneration stream is allowed to enter the adsorption gas contactor, the regeneration stream is controlled so that the steam partial pressure of the regeneration stream is equal to or greater than 0.3 bar absolute.
48. The adsorption gas separation method of claim 41, further comprising a step (d) after step (c), wherein: The step (d) includes: exposing the solid adsorbent to a third relative humidity, the third relative humidity being less than the second relative humidity; forming a third product stream; and recovering the third product stream from the adsorption gas contactor.
49. The adsorptive gas separation method of claim 48, further comprising: In step (d), a conditioning stream is passed into the adsorption gas contactor, the conditioning stream comprising at least one of an air stream, an inert gas stream, and a nitrogen stream.
50. The adsorption gas separation method according to any one of claims 41 to 49, wherein: In step (b), passing the multicomponent fluid stream through the adsorptive gas contactor comprises contacting the solid adsorbent with the multicomponent fluid stream at a pressure between about 1 bar absolute and about 2 bar absolute.
51. The adsorption gas separation method according to any one of claims 41 to 50, wherein: In step (b), passing the multicomponent fluid stream through the adsorption gas contactor includes passing the multicomponent fluid stream through the adsorption gas contactor at a temperature between about 10°C and about 90°C.
52. The adsorption gas separation method according to any one of claims 41 to 51, wherein: The multi-component fluid stream is at least one of an air stream, a combustion gas stream, a flue gas stream, an acid gas stream, and / or a process gas stream.
53. The adsorptive gas separation method of claim 52, wherein: The multi-component fluid stream comprises water or steam.
54. The adsorptive gas separation method according to any one of claims 41 to 53, wherein: The first component is carbon dioxide, sulfur dioxide or nitrogen oxides, and the second component is nitrogen.
Citation Information
Patent Citations
Adsorptive gas separation process and system
WO2017165974A1
Parallel passage contactor having active layers
WO2021240476A1